Analisis Historis Sebagai Instrumen Kritik Matan Hadis - Tasbih Tasbih (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
The main function of haditz critic is to ensure originality and validity of the haditz. Its objective is the core content (matan) a haditz. Historical analysis is used to examine validity. Historical analysis therefore is so vipotal. This is because it is associated with recognition of the authenticity and validity of honor haditzs. It is because human social-interaction associated with its environment and history. Consequently, if a hadith contradicts with historical facts, then a haditz does not meet the rules of validity; as result, the haditz can be classiefied weak (daif). Thus, historical analysis is useful to show the weakness and falsehood of a haditz.